Poly-herbal tablet formulation by design expert tool and in vitro anti-lipase activity - Amruta Balekundri; Amit Shahapuri; Mrityunjaya Patil (SpringerOpen, 2020)
Abstract Background Traditional medicine being ethnic is preferred worldwide even in these modern days. Obesity is a lifestyle disorder. Many chemically synthesized medicines are available. Poly-herbal medicines can be one of the safest alternatives with less side effects in treating obese patients. Results The in vitro anti-lipase activity was carried out for a different concentration. The formulation of the poly-herbal tablets was designed using the Design Expert software. The pre-compression and post-compression studies show that the formulation F6 showed better results of all the formulations designed. Stability study results showed that the poly-herbal tablets were stable throughout the studies. Conclusion The results show that F6 is the better formulation based on the tablet evaluation, and all the extracts showed inhibitory activity against pancreatic lipase indicating its active role in the treatment of obesity.